Anti-prothrombin (aPT) and anti-phosphatidylserine/prothrombin (aPS/PT) antibodies and the risk of thrombosis in the antiphospholipid syndrome - Sciascia, Savino; Sanna, Giovanni; Murru, Veronica; Roccatello, Dario; Khamashta, Munther A.; Bertolaccini, Maria Laura (Thrombosis and Haemostasis, 2014)
Antibodies to prothrombin are detected by directly coating prothrombin on irradiated ELISA plates (aPT) or by using the phosphatidylserine/ prothrombin complex as antigen (aPS/PT). Although these antibodies have both been associated with antiphospholipid syndrome (APS) and a correlation between the two assays have been reported, it seems that aPT and aPS/PT belong to different populations of autoantibodies. It was our objective to systematically review the available evidence on aPT and aPS/PT antibodies and the risk of thrombosis in APS. Medline-reports published between 1988 and 2013 investigating aPT and aPS/PT as a risk factor for thrombosis were included. Whenever possible, antibody isotype(s) and site of thrombosis were analysed. This systematic review is based on available data from more than 7,000 patients and controls from 38 studies analysing aPT and 10 aPS/PT. Antibodies to prothrombin (both aPT and aPS/PT) increased the risk of thrombosis (odds ratio [OR] 2.3; 95% confidence interval [CI] 1.72–3.5). aPS/PT seemed to represent a stronger risk factor for thrombosis, both arterial and/or venous than aPT (OR 5.11; 95%CI 4.2–6.3 and OR 1.82; 95%CI 1.44–2.75, respectively). In conclusion, routine measurement of aPS/PT (but not aPT) might be useful in establishing the thrombotic risk of patients with previous thrombosis and/or systemic lupus erythematosus. Their inclusion as laboratory criteria for the APS should be indisputably further explored.
Keywords: Antiphospholipid antibodies; antiphospholipid syndrome; venous thrombosis; stroke